2021
DOI: 10.1111/wbm.12236
|View full text |Cite
|
Sign up to set email alerts
|

Seed dynamics of Aeschynomene denticulata and Aeschynomene indica

Abstract: Jointvetch (Aeschynomene spp., Fabaceae) is considered a problematic broadleaf weed for rice production in Brazil, the United States, and Asia. Seed dormancy is particularly important for the perpetuation of annual weeds, representing the only link between different generations and thus the source of all future weed infestations. Seed dynamics in annual species are complex and related to many biotic and abiotic factors. The objectives of this study were to determine whether dormancy occurs in Aeschynomene dent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The germination of Indian jointvetch seeds mainly depends on the temperature during the day [ 5 ]. Research has shown that the seeds of Indian jointvetch have dormancy characteristics, which can survive for about six months in the soil seed bank and mechanical scarification is an effective method to break dormancy [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The germination of Indian jointvetch seeds mainly depends on the temperature during the day [ 5 ]. Research has shown that the seeds of Indian jointvetch have dormancy characteristics, which can survive for about six months in the soil seed bank and mechanical scarification is an effective method to break dormancy [ 6 ].…”
Section: Introductionmentioning
confidence: 99%